Phosphomimetic Mutation of the N-Terminal Lid of MDM2 Enhances the Polyubiquitination of p53 through Stimulation of E2-Ubiquitin Thioester Hydrolysis. Issue 8 (24th April 2015) - Fraser, Jennifer A.; Worrall, Erin G.; Lin, Yao; Landre, Vivien; Pettersson, Susanne; Blackburn, Elizabeth; Walkinshaw, Malcolm; Muller, Petr; Vojtesek, Borek; Ball, Kathryn; Hupp, Ted R.
Abstract: Mouse double minute 2 (MDM2) has a phosphorylation site within a lid motif at Ser17 whose phosphomimetic mutation to Asp17 stimulates MDM2-mediated polyubiquitination of p53. MDM2 lid deletion, but not Asp17 mutation, induced a blue shift in the λmax of intrinsic fluorescence derived from residues in the central domain including Trp235, Trp303, Trp323, and Trp329. This indicates that the Asp17 mutation does not alter the conformation of MDM2 surrounding the tryptophan residues. In addition, Phe235 mutation enhanced MDM2 binding to p53 but did not stimulate its ubiquitination function, thus uncoupling increases in p53 binding from its E3 ubiquitin ligase function. However, the Asp17 mutation in MDM2 stimulated its discharge of the UBCH5a-ubiquitin thioester adduct (UBCH5a is a ubiquitin-conjugating enzyme E2D 1 UBC4/5 homolog yeast). This stimulation of ubiquitin discharge from E2 was independent of the p53 substrate. There are now four known effects of the Asp17 mutation on MDM2: (i) it alters the conformation of the isolated N-terminus as defined by NMR; (ii) it induces increased thermostability of the isolated N-terminal domain; (iii) it stimulates the allosteric interaction of MDM2 with the DNA-binding domain of p53; and (iv) it stimulates a novel protein–protein interaction with the E2-ubiquitin complex in the absence of substrate p53 that, in turn, increases hydrolysis of the E2-ubiquitin thioester bond. These data also suggest a new strategy to disrupt MDM2 function by targeting the E2-ubiquitin discharge reaction. Graphical Abstract: Highlights: Phosphomimetic mutation in MDM2 stimulates polyubiquitination of p53. Intrinsic fluorescence was used to identify an effect of the MDM2 pseudo-substrate "lid" motif on central domain MDM2 conformation. A novel mutation (W235F) in the acidic domain of MDM2 uncoupled enhanced p53 binding from MDM2 ubiquitination activity. A novel p53-independent effect of lid mutation on MDM2 was identified in the E2-ubiquitin complex.